Following Continuity and Change: Italy’s View on European Neighborhood Policy Towards Ukraine - Vdovychenko, V. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
Current EU economic and security challenges on the territory of the EU’s ‘ring of friends’ open a new page of its history influencing European security and stability framework of development. Therefore, it’s crucial to understand circumstances that favored to the catalyst progress of unstable neighborhoods. The article presents an analysis of the Italy’s position towards European Neighborhood Policy and the Eastern dimension of this policy — Eastern Partnership. A special interest is focus on its view towards Ukraine, being a reality-check for the European Union officials after the Revolution of Dignity, the illegal annexation of Crimea and the hybrid war of Russia. This article is presenting the ideas that ENP was created by the EU as an instrument for the democratization which couldn’t prevent conflicts in the geopolitically diverse regions. Italy, being one of the founding members of the European Union, was reluctant advocate a balanced approach towards the neighborhood regions. It merely focused on the Southern dimension of the ENP, almost taking apart Eastern Partnership. In the first part, the article demonstrates the development process of the ENP with a special attention that it coincided with the EU 5th enlargement preparation. This dualism influenced on the ENP tailoring and subsequent implementation. The second part focuses on the of the Italy’s opinion development from ENP launch till 2009 when its Eastern dimension — Eastern Partnership — was introduced. The third part analyzes Italy’s perception of Eastern Partnership and its attempts to reschedule EU’s attention to the South flank of the ENP in the post-Crimea annexation period.